QUO VADIS HUKUMAN PIDANA KEBIRI KIMIA BAGI PELAKU KEJAHATAN SEKSUAL PADA ANAK DI INDONESIA - Asokawati, Ainunnisa Rezky (Journal of Islamic Law Studies, 2020)
Sexual assault committed against children become one of the polemics in the society. The government as the state protector accommodates the polemic by making the law in form of Law Number 17 of 2016 concerning the Stipulation of Government Regulation in place of Law Number 1 of 2016 concerning Second Amendment to Law Number 23 of 2002 concerning Child Protection. The regulation accommodated the society’s need by arranging punishment for the perpetrators of sexual assault affecting children cases. Article 81 of Law Number 35 of 2014 in the form of first amendment to the Child Protection Law concerning criminal threats against perpetrators who gives violence threat or do violence by forcing children to have intercourse, has given the punishment of imprisonment, fines, even chemical castration. The chemical castration gives a new polemic in the implementation, because it must be done by the medical personnel, in this case appointing doctors as executors. Ikatan Dokter Indonesia (IDI) considers that it cannot appoint doctors as executors because it is against the code of medical ethics. Therefore, this article will discuss criminal penalties for perpetrators of sexual assault against children according to Indonesian law, Islamic law, and their comparison with the South Korean state.